Influence of the directives of the wide field of applied social sciences guidelines on Qualis scientific Management journals - Maccari, Emerson Antonio; Hsu, Pang Lien; Storopoli, José Eduardo; Silva, Altiéres de Oliveira (Revista de Administração da UFSM, 2018)
This study aims to analyze the composition of the Qualis Journals for the fields comprising the wide range of applied social sciences and their influence on Qualis Journals on management. For this purpose, we sought secondary data from reports and documents in the field obtained from the CAPES and Education Ministry websites regarding the evaluation and Qualis criteria in additions to articles in which this subject is discussed. The results show that the criteria used in management are different from the other fields, which converge with one another. The results also show that most of the regular A1 journals of the entire field of applied social sciences are published in english language. We concluded that the management criteria are quite different from the criteria used in the other fields and propose further discussions.